Synthesis of Methanethiol from Methanol and Carbon Disulfide over CoKW/Al2O3 Catalysts: The Possible Reaction Network and Reaction Mechanism. Issue 33 (6th September 2018) - Wang, WeiMing; Li, JianJun; He, QiuJin; Peng, Shuai; Yang, YiQuan; Li, Ming
Abstract: Synthesis of methanethiol from methanol and carbon disulfide was catalyzed by KW/γ‐Al2 O3 catalysts under different reaction conditions. A possible reaction network was put forward by investigating the effects of the molar ratio of reactants, the reaction pressure, the reaction temperature, the residence time, and in the presence of water and hydrogen sulfide on the catalytic performance. Furthermore, the relationship between the conversion of CH3 OH, the yield of CH3 SH and the surface acid‐base properties was discussed in detail. The catalytic results measured in the laboratory scale (2 ml catalysts) and those obtained in the scaling‐up tests (50 ml original grain catalysts) are well matched. Combined with pyridine adsorption Fourier Transform Infrared (FT‐IR), CO2 /NH3 ‐Temperature Programmed Desorption (CO2 /NH3 ‐TPD), and the catalytic results, it was found that the conversion of CH3 OH can be chiefly correlated with weak and moderate acid sites, while the selectivity toward CH3 SH is mainly related to the weak basic sites, and the possible reaction mechanism was put forward. Abstract : Authors employed CS2, as starting S precursor, to react with methanol for synthesizing CH3 SH. The selectivity toward CH3 SH and conversion of CH3 OH remained stable throughout the entire 300 hours over the CoKW/Al2 O3 catalyst. The more the Lewis acidic sites, the higher the CH3 OH conversion. The more the weak base sites, the higher the CH3 SH yield.